Assessment of Bacopa caroliniana to sequester landfill heavy metals contaminant via in vitro hybrid model system - Othman, Rashidi; Mat Ali, Qurratu Aini; Hj. Baharuddin, Zainul Mukrim; Sahidin, Norhanizan (2015)
Most of developing countries used to develop various technologies to decrease the percentage of heavy metals contaminant from landfill site such as incineration, solvent extraction, soil washing by using physical separation methods or chemical agents, solidification or stabilization technology, indirect thermal treatment, soil venting, membrane technology and industrial water treatment. However, these approaches are expensive, difficult to apply in huge scale area and also may cause great environmental impact as it affects soil structure and fertility and biological activity. Therefore, one of the effective approach to control this matter is by using natural treatment. Phytoremediation is one of the natural ways for landfill treatment by using plants and is proven to be an economically competitive and eco-friendly to the environment as it does not require additional energy or substantial material just a small mechanical apparatus to operate it. Therefore, the study aimed to evaluate heavy metals sequestration rate of Bacopa caroliniana at three different concentrations ranging from low, medium and high (0.5 mol, 1.0 mol and 2.0 mol) of hybrids heavy metals from Al, Fe, Mn, and Mg at four different period of time (week 1 until week 4) through in vitro model system. The results showed that there were significant differences between the sequestration rates of different heavy metal hybrids and B. caroliniana in removing the contaminants. Thus, this species is strongly supported the phytoremediation approach in remediating the landfill heavy metals contaminant.